2014
DOI: 10.15517/rbt.v62i0.16275
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of macroinvertebrates on intertidal rocky shores in Gorgona Island, Colombia (Tropical Eastern Pacific)

Abstract: Abstract:Organisms found on rocky shores must endure harsh environmental conditions during tidal changes but scientific studies on tropical rocky shores are scarce, particularly in Colombian shores. Here we describe the spatial distribution of macroinvertebrates associated to the intertidal rocky ecosystems of Gorgona island, Colombia (Tropical Eastern Pacific). Sampling was carried out in four localities around the island: La Ventana and La Camaronera (sampled during October 2010) and La Mancora and El Muelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
2
4
0
5
Order By: Relevance
“…(C) of the Family Cerethiopsidae in association with algal community. Various studies on gastropod assemblage showed diversity of gastropods in the intertidal habitats [13][14][15][16] similar in this study with the use of diversity indices. However, the types of substrate vary from fine sand coral reef flats [13] and rocky shore beaches [9], including intertidal rocky shores [14,15] and generally the intertidal zone of mixed substrate [6,11].…”
Section: Sampling Identification and Field Collectionsupporting
confidence: 80%
See 4 more Smart Citations
“…(C) of the Family Cerethiopsidae in association with algal community. Various studies on gastropod assemblage showed diversity of gastropods in the intertidal habitats [13][14][15][16] similar in this study with the use of diversity indices. However, the types of substrate vary from fine sand coral reef flats [13] and rocky shore beaches [9], including intertidal rocky shores [14,15] and generally the intertidal zone of mixed substrate [6,11].…”
Section: Sampling Identification and Field Collectionsupporting
confidence: 80%
“…Various studies on gastropod assemblage showed diversity of gastropods in the intertidal habitats [13][14][15][16] similar in this study with the use of diversity indices. However, the types of substrate vary from fine sand coral reef flats [13] and rocky shore beaches [9], including intertidal rocky shores [14,15] and generally the intertidal zone of mixed substrate [6,11]. Results of gastropod diversity study in Sombu Beach, Wakatobi, Indonesia showed 13 species of classes of gastropods covering only a month of study however using more transects [13] while a 3 year study of monthly sampling but using only one transect with 31 identified species.…”
Section: Sampling Identification and Field Collectionsupporting
confidence: 80%
See 3 more Smart Citations